(untitled) - Campione, Mary (Reading, Massachusetts, 1996)
The book introduces the fundamental concepts of the Java Titorial and its applications. It explains the nuts and bolts of the language, applet construction, and the core Java classes
Keywords: Java (Ngôn ngữ chương trình máy tính),Java (Computer program language),Object-oriented programming (Computer science)